INTEGRASI MANAJEMEN KURIKULUM PAUD DENGAN EKSPLORASI BUDAYA LOKAL UNTUK MENANAMKAN NILAI PANCASILA - Sari, Fidiyah; Salistina, Dewi; Nai'mah, Nai'mah (Raudhah - Proud To Be Professional, 2024)
This study aims to integrate early childhood education (PAUD) curriculum management with local cultural exploration as an effort to instill Pancasila values ??in early childhood. Through a qualitative approach, this study explores ways in which local cultural elements can be integrated into the curriculum to enrich the learning process and shape children's character in accordance with Pancasila values. The results of the study indicate that the introduction of local culture in learning activities increases children's engagement and their understanding of cultural heritage and is effective in internalizing the moral and social values ??contained in Pancasila. Recommendations are given to educators to be more active in integrating local culture into daily learning practices, as well as to policy makers to support this initiative through the preparation of relevant policies and support facilities. This study concludes that the integration of local culture in the PAUD curriculum can contribute significantly to the formation of children's character based on Pancasila values. Keywords: Curriculum Management, Local Cultural Exploration, Pancasila Values ??AUD